Normative Analysis of Prevention of Re-Traumatization of Child Victims in Criminal Justice Proceedings on Standards of Examination and Protection of Children's Rights - Yusuf Hanafi Pasaribu (Greenation International Journal of Law and Social Sciences, 2026)
This study examines the Prevention of re-traumatization (re-trauma) in child victims in the criminal justice process. Re-Trauma arises when the child is forced to repeat events, face pressing or entangling questions, meet the perpetrator, or his identity is exposed. The research uses normative legal methods with legislation, conceptual, and case approaches. Primary legal materials include the SPPA law, the child protection law, the Criminal Procedure Code, The Witness and Victim Protection Law, and the TPKS law, with illustrations of the verdict the results of the study show that Indonesian law already contains minimum standards: confidentiality of identity, assistance, Prohibition of entangling questions, as well as the option of electronic recording and audiovisual examination to reduce repeated examinations. The main obstacle is the lack of uniform technical guidelines and coordination between officials, so that protection can vary between cases. Research confirms the Prevention of re-trauma is not an issue of psychology alone, but rather a standard procedure that can be measured clearly.